2015
DOI: 10.1371/journal.pone.0139404
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction in Risky Environments: The Role of Invasive Egg Predators in Ladybird Laying Strategies

Abstract: Reproductive environments are variable and the resources available for reproduction are finite. If reliable cues about the environment exist, mothers can alter offspring phenotype in a way that increases both offspring and maternal fitness (‘anticipatory maternal effects’—AMEs). Strategic use of AMEs is likely to be important in chemically defended species, where the risk of offspring predation may be modulated by maternal investment in offspring toxin level, albeit at some cost to mothers. Whether mothers adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 111 publications
(112 reference statements)
2
7
0
Order By: Relevance
“…One explanation may be found in the trend for a greater number of eggs to be laid in the presence of predator cues, reflecting results from previous studies where A. bipunctata laid a larger number of eggs in response to the same stimulus (Paul et al, 2015). This suggests that females may have been constrained from any concomitant increase in investment in egg alkaloid level (Smith and Fretwell, 1974), resulting in the lack of increase in egg alkaloid level when aphids were absent but predator cues were present (i.e., P+/A−).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…One explanation may be found in the trend for a greater number of eggs to be laid in the presence of predator cues, reflecting results from previous studies where A. bipunctata laid a larger number of eggs in response to the same stimulus (Paul et al, 2015). This suggests that females may have been constrained from any concomitant increase in investment in egg alkaloid level (Smith and Fretwell, 1974), resulting in the lack of increase in egg alkaloid level when aphids were absent but predator cues were present (i.e., P+/A−).…”
Section: Discussionsupporting
confidence: 64%
“…The A. bipunctata eggs used for the trial were collected from culture and frozen at −80 • C for 12 months. Quantification of egg (-)-adaline content is destructive, but within-female repeatability of egg (-)-adaline content and egg mass is high (Paul et al, 2015). The values of egg (-)-adaline and egg mass from previously analyzed eggs (Paul et al unpublished data) were therefore used as proxy values for the females that laid them and used to select remaining unanalysed eggs for the cannibalism trials.…”
Section: Cannibalism Experimentsmentioning
confidence: 99%
“…For example, fruit fly ( Drosophila sp.) and ladybird beetle (Adalia bipunctata) females altered timing of egg laying and total egg number under conditions of simulated predation risk . Similarly, we found that female Q‐flies laid fewer eggs when predators were present.…”
Section: Discussionmentioning
confidence: 54%
“…The presence of predators is known to influence the egg‐laying behaviour of a number of prey species . For example, fruit fly ( Drosophila sp.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation